Have Macroeconomic Models Lost Their Connection with Economic Reality? - Tom van Veen (Center for Economic Studies and ifo Institute (CESifo), 2020)
Macroeconomic theory has developed into increasingly sophisticated mathematical models. In the words of Mankiw, macroeconomics has developed from engineering into science. The Global Financial Crisis (GFC) revealed that the empirical relevance and the usefulness of these models is debatable. Why has this occurred? Who have been the key players in this development? What have been the policy implications of this development? This paper addresses these points by providing an overview of the development of macroeconomic theory over the past 40 years. The focus is on the main lines of thinking and the story behind the models more so than on the mathematical details of these models. I argue that crises have been the main driver of changes in macroeconomic theory and that the current debates after the GFC will be the start of a more plural approach to macroeconomics, in which engineers will regain their place.
Keywords: B22; E12; E60; 330; macroeconomic theory; Keynes; Friedman; Lucas